Growth and nutritional values of Moina micrura fed on Chlorella vulgaris grown in digested palm oil mill effluent - Habib, M. A. B.; Md. Yusoff, Fatimah; Phang, Siew Moi; Mohamed, Suhaila (Asian Fisheries Society, 2003)
Moina micrura Kruz (Isolate no. AR001), a cladoceran and an important aquaculture feed, was cultured on Chlorella vulgaris Beijerinck (Isolate no. 001) grown in 10 and 20% digested palm oil mill effluent (POMED) and inorganic fertilizer (N:P:K = 1:1:0.50) in 70 l tanks. The collected microalgae was distributed to M. micrura twice daily at the rate of 3% dry body weight for 14 days. The specific growth rate of M. micrura was significantly higher (p<0.05) when fed on microalgae grown in 10% POMED than fed on the same cultured in 20% POMED and fertilizer. The protein and lipid contents were significantly higher (p<0.05) in M. micrura fed on microalgae grown in 10% POMED than in those fed on this microalgae cultured in other media. The essential amino acids such as histidine, arginine, threonine, phenylalanine, valine, methionine, lysine and tryptophan of C. vulgaris grown in 10% POMED enhanced the accumulation of these EAAs in M. micrura. The C18, C20 and C22 polyunsaturated fatty acids (PUFAs) viz. linolenic acid (18:3n-3), ¡ linolenic acid (18:3n- 6), eicosatrienoic acid (20: 3n-6), arachidonic acid (20: 4n-6), EPA (20: 5n-3), DPA (22: 5n-3) and DHA (22: 6n-3) of C. vulgaris grown in 10% POMED enhanced the levels in M. micrura. The PUFAs were found significantly higher (p<0.05) in M. micrura fed on C. vulgaris cultured in 10% POMED followed by 20% POMED and only inorganic fertilizer. Most of the essential minerals were present in high amount in M. micrura fed on this algae grown in 20% and then 10% POMED followed by fertilizer. The characteristics of effluents PDF created with pdfFactory Pro trial version www.pdffactory.com 108 and mineral contents were reduced at least 10 to 12 times after growing C. vulgaris, which indicate the suitability of the supernatant of residues to release in the waterways. This study showed that the nutritional values of M. micrura were dependent on the nutritional values of the feed, C. vulgaris.